Association between physical activity and all-cause mortality in patients with depression: a prospective cohort study based on NHANES data - Xiao, Jiaqiang; Dong, Xiaosheng; Ding, Meng; Yang, Qingqing; Kong, Tao (Frontiers in Public Health, 2025)
ObjectiveThis prospective cohort study aimed to investigate the association between physical activity (PA) and all-cause mortality in patients with depression.MethodsData from 2,841 subjects were derived from the 2005–2018 U.S. National Health and Nutrition Examination Survey (NHANES), which included 13 years of follow-up. Depression was assessed using the Patient Health Questionnaire-9 (PHQ-9). The relationships between different amounts and types of physical activity (PA, such as work, transport, or leisure) and all-cause mortality were analyzed using multivariate Cox proportional hazard regression models and restricted cubic splines.ResultsAfter adjusting for all covariates, the depressed patients who engaged in sufficient PA (≥600 metabolic equivalent (600 MET)-min/week) showed a 40% (hazard ratio [HR] = 0.60, 95% confidence interval [CI]: 0.47–0.76) lower mortality risk compared to their physically inactive counterparts. The mortality rate from recreational PA continues to decline with increasing proportions. Subgroup analyses further revealed sustained benefits in vulnerable populations: stroke patients maintaining sufficient PA achieved a HR of 0.40 (95% CI: 0.18–0.88) for all-cause mortality, while those with cardiac conditions showed an even more pronounced HR of 0.35 (95% CI: 0.16–0.77).ConclusionPA has a positive effect on reducing the risk of death in patients with depression, and there are differences in the effectiveness of different volumes and purposes (for work, leisure, or transport) of PA in relation to reducing the risk of death. These findings emphasize the critical role of PA in mitigating mortality risk among individuals with depression, promoting personalized exercise plans that consider differences in activity volume and purposes.